(untitled) (Revista Internacional de Folkcomunicação, 2025)
Reginaldo de Túlio, a resident of the Heliópolis favela in São Paulo, is the president of Cine Favela, one of the largest sociocultural institutions for cinema, social assistance and culture in the outskirts of the city.